Deep Learning Models for Coronary Atherosclerosis Detection in Coronary CT Angiography - Laidi, Amel; Ammar, Mohammed; Daho, Mostafa EL Habib; Mahmoudi, Said (Current Medical Imaging, 2024)
Background Patients with atherosclerosis have a rather high risk of showing complications, if not diagnosed quickly and efficiently. Objective In this paper we aim to test and compare different pre-trained deep learning models, to find the best model for atherosclerosis detection in coronary CT angiography. Methods We experimented with different pre-trained deep learning models and fine-tuned each model to achieve the best classification accuracy. We then used the Haar wavelet decomposition to improve the model’s sensitivity. Results We found that the Resnet101 architecture had the best performance with an accuracy of 95.2%, 60.8% sensitivity, and 90.48% PPV. Compared to the state of the art which uses a 3D CNN and achieved 90.9% accuracy, 68.9% Sensitivity and 58.8% PPV, sensitivity was quite low. To improve the sensitivity, we chose to use the Haar wavelet decomposition and trained the CNN model with the module of the three details: Low_High, High_Low, and High_High. The best sensitivity reached 80% with the CNN_KNN classifier. Conclusion It is possible to perform atherosclerosis detection straight from CCTA images using a pretrained Resnet101, which has good accuracy and PPV. The low sensitivity can be improved using Haar wavelet decomposition and CNN-KNN classifier.
Keywords: Wavelet decomposition